An overview of the fauna of Embioptera (Insecta) in Brazil - Krolow, Tiago Kütter (2024)
Data from the Taxonomic Catalog of the Brazilian Fauna provides an historical review of Embioptera diversity and distribution in Brazil and allow to understand the knowledge of species diversity in thisoligodiverse order of insects. Brazilian embiopterans represent around 10% of the world’s fauna with a total of 58 species in five families. Of these species, around 64% are known only for Brazilian territory, while another 36% are shared with neighboring countries. Archembiidae is the most species-rich family (32 spp.) followed by Anisembiidae (13 spp.), Teratembiidae (7 spp.), Clothodidae (5 spp.) and the invasive Oligotomidae (1 sp.). Brazil has never had a taxonomist in the order and it was only in 2016 that the first species was described by Brazilian researchers. Two foreign researchers are responsible for describing approximately 80% of the speciesrecorded in Brazil. Brazilian institutions keep 52% of the primary types of the species of Embioptera that occur in Brazil, while 38% were deposited in USA and 10% in Europe. About distribution records, only two Brazilian states (Amazonas and Pará) have more than 10 known species, and in four states the order has not yet been formally registered. Amazonia is the most diverse biome, followed by Atlantic Forest and Cerrado. Despite of the little knowledge about Embioptera in Brazil, it is expected that the expansion of sampling and the training of specialized human resources will be responsible for expanding data on the diversity and distribution of the order in the near future.